Joint Seismic and Gravity Data Inversion to Image Intra-Crustal Structures: The Ivrea Geophysical Body Along the Val Sesia Profile (Piedmont, Italy) - Scarponi, Matteo; Hetényi, György; Plomerová, Jaroslava; Solarino, Stefano; Baron, Ludovic; Petri, Benoît (Frontiers in Earth Science, 2021)
We present results from a joint inversion of new seismic and recently compiled gravity data to constrain the structure of a prominent geophysical anomaly in the European Alps: the Ivrea Geophysical Body (IGB). We investigate the IGB structure along the West-East oriented Val Sesia profile at higher resolution than previous studies. We deployed 10 broadband seismic stations at 5 km spacing for 27 months, producing a new database of ~ 1000 high-quality seismic receiver functions (RFs). The compiled gravity data yields 1 gravity point every 1-2 km along the profile. We set up an inversion scheme, in which RFs and gravity anomalies jointly constrain the shape and the physical properties of the IGB. We model the IGB’s top surface as a single density and shear-wave velocity discontinuity, whose geometry is defined by four, spatially variable nodes between far-field constraints. An iterative algorithm was implemented to efficiently explore the model space, directing the search towards better fitting areas. For each new candidate model, we use the velocity-model structures for both ray-tracing and observed-RFs migration, and for computation and migration of synthetic RFs: the two migrated images are then compared via cross-correlation. Similarly, forward gravity modelling for a 2D density distribution is implemented. The joint inversion performance is the product of the seismic and gravity misfits. The inversion results show the IGB protruding at shallow depths with a horizontal width of ~ 30 km in the western part of the profile. Its shallowest segment reaches either 3-7 or 1-3 km depth below sea-level. The latter location fits better the outcropping lower crustal rocks at the western edge of the Ivrea-Verbano Zone. A prominent, steep eastward-deepening feature near the middle of the profile, coincident with the Pogallo Fault Zone, is interpreted as inherited crustal thickness variation. The found density and velocity contrasts of the IGB agree with physical properties of the main rock units observed in the field. Finally, by frequency-dependent analysis of RFs, we constrain the sharpness of the shallowest portion of the IGB velocity discontinuity as a vertical gradient of thickness between 0.8 km and 0.4 km.